The man who found time : James Hutton and the discovery of the Earth's antiquity - Repcheck, Jack.; Pocket Books (London : Simon & Schuster, 2003)
Chronicles the life of James Hutton, discussing how he changed society's understanding of the earth and its dynamic forces by proving that the earth was likely millions of years old and was continuously being shaped and re-shaped by everyday forces.
Includes index (p.235-247).
Adult
Keywords: Hutton, James, -- 1726-1797.; Geologists -- Scotland -- Biography; Geology -- History